The Influence of Technological and Information Advances on Local Culture for Generation Z - Marsela Arsya Sakinah (SAINTEKBU, 2023)
The development of information technology is moving increasingly rapidly so its existence provides benefits and impacts on daily life. With the existence of information technology, it makes it easier to access information dissemination without knowing space and time. In terms of culture, information technology is one of the factors that influences the existence of local culture. Local culture, which is starting to fade, is influenced by the existence of information technology. To maintain culture, future generations are needed to continue preserving culture. Therefore, more in-depth research is needed that is targeted at the next generation, namely Generation Z, to find conclusions regarding the influence of advances in information technology on culture for Generation Z. This must be proven by research involving Generation Z as respondents. From the results of data collection, it is necessary to take the percentage and average of respondents' answers using a Likert scale. The Likert scale is used as a reference in research using quantitative methods. Using quantitative methods involved 79 respondents to conclude. It was concluded that Generation Z tends to frequently use information technology devices, meaning that Generation Z is more aware of renewable technology and tends to make less use of the presence of technology to preserve and maintain the existence of local culture.